The Effect of Perceived Enjoyment and Social Interaction on Continuance Intention Through User Satisfaction Among Valorant Players in Bandung City - Afif Nasywa Ramadhan; Faizal Fardhani Sigarlaki (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the effect of perceived enjoyment and social interaction on continuance intention through user satisfaction among Valorant players in the city of Bandung. This research is motivated by the decline in Valorant's global monthly active player count, from approximately 24–25 million in mid-2024 to 17–20 million by the end of 2025, as well as the fluctuating pattern of information searches about Valorant in Indonesia, which indicates an issue with players' continuance intention. This study uses a quantitative approach with a survey method. The research sample consisted of 116 respondents selected using a purposive sampling technique, with the criteria of being at least 17 years old, having played Valorant at least once in the last three months, and residing in the city of Bandung. Data were analyzed using multiple linear regression and the Sobel test with the assistance of SPSS version 25. The results show that perceived enjoyment and social interaction have a positive and significant effect on user satisfaction, and user satisfaction has a positive and significant effect on continuance intention. Directly, only social interaction has a significant effect on continuance intention, while perceived enjoyment has no significant direct effect and is thus fully mediated by user satisfaction, whereas the effect of social interaction is partially mediated. These findings indicate that enjoyment in playing only drives continuance intention after being processed through satisfaction, whereas social interaction drives that intention both directly and through user satisfaction. This study reinforces the integration of the Expectation Confirmation Model, the concept of a hedonic information system, and self-determination theory in the study of post-adoption user behavior in online games. The findings can serve as input for Riot Games and other stakeholders in the competitive gaming industry in designing player retention strategies that emphasize playing enjoyment, the quality of social interaction, and user satisfaction.